Counter hegemony of beauty concept by The Body Shop Instagram ad: A semiotic analysis - Widuri, Rachma Tri; Budipratiwi, Rizki Ayu; Citrayomie, Ayoedia Gita (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
Western beauty standards have dominated the perception of Indonesians for so long. It is mentioned that beautiful women should have smooth white skin, pointy noses, tall bodies, and straight hair. This view has also been the guideline for beauty product manufacturers in producing and advertising their cosmetics. Therefore, conventional cosmetics advertising models are usually white skinned women that have wide eyes, tall bodies, and straight hair. This study aims to describe how The Body Shop tries to fight against the hegemony of the concept of beauty that has dominated before, which called counter hegemony. This research is a descriptive qualitative research that using Charles Sanders Pierce's semiotic analysis method, which focuses on the sign (representant), the meaning of the sign (interpretant), and the object. The research based on six photos and advertising narrations that aired on Instagram @thebodyshopindo on October 9, 2021. The results showed that The Body Shop has countered the hegemony of the dominant beauty concept by displaying signs of resistance in the form of a firm narrative which means inviting women to always believe. themselves with their natural beauty, not pursuing flawless white skin. The object is a female model with dark skin, not slim, and not smooth.